A Strategy For Developing The Unorganized Food Industries Sector In Syria (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study reviews the phenomenon of the unorganized food industrial sector, which is considered one of the most important economic issues due to its spread in sufficient geographical areas and despite the importance of this topic, but the studies that study this in this regard remain very few and are insufficient to support any plan aimed at organizing and developing This sector.This study examines the concept of the unorganized sector in its general form down to the unorganized food industries sector, the components of this sector and its outputs of activities and services, the reasons that stimulate the existence and growth of these unorganized industries and its relationship to the economic level of individuals and what steps should be taken to organize these industries. Analyzing its problems and development potentials through framing and legalizing it with the aim of improving sector performance and organization, and developing productivity and quality.